Crucial role of the intracellular α-glucosidase MalT in the activation of the transcription factor AmyR essential for amylolytic gene expression in Aspergillus oryzae. Issue 9 (10th July 2021) - Ichikawa, Takanori; Tanaka, Mizuki; Watanabe, Takayasu; Zhan, Sitong; Watanabe, Akira; Shintani, Takahiro; Gomi, Katsuya
ABSTRACT: We examined the role of the intracellular α-glucosidase gene malT, which is part of the maltose-utilizing cluster ( MAL cluster) together with malR and malP, in amylolytic gene expression in Aspergillus oryzae. malT disruption severely affected fungal growth on medium containing maltose or starch. Furthermore, the transcription level of the α-amylase gene was significantly reduced by malT disruption. Given that the transcription factor AmyR responsible for amylolytic gene expression is activated by isomaltose converted from maltose incorporated into the cells, MalT may have transglycosylation activity that converts maltose to isomaltose. Indeed, transglycosylated products such as isomaltose/maltotriose and panose were generated from the substrate maltose by MalT purified from a malT -overexpressing strain. The results of this study, taken together, suggests that MalT plays a pivotal role in AmyR activation via its transglycosylation activity that converts maltose to the physiological inducer isomaltose. Graphical Abstract: